Exchange rate forecasting with information flow approach - Balčiūnas, Andrius; Mačerinskienė, Irena (Business: Theory and Practice, 2016)
The purpose of this article is to assess exchange rate forecasting possibilities with an information flow approach model. In the model the three types of information flows are distinguished: fundamental analysis information flow through particular macroeconomic determinants, microstructure approach information flow through dealer clients’ positioning data, technical analysis information flow through technical indicators. By using regression analysis it is shown that the composed model can forecast the exchange rate, the most significant information flows are distinguished. The results lead to further development of the information flow approach as a tool to forecast exchange rate fluctuations.